Modelowanie rozkładu strat w pomiarze ryzyka operacyjnego - Kuziak, Katarzyna (Loss Distribution Approach for Operational Risk Measurement, 2008)
In the operational risk measurement we use stochastic modelling approach, where the parameter estimation of probability distribution for the frequency of events and for the severity is made by empirical estimation or parametric estimation (e.g. loss distribution approach, LDA). In this paper the loss distribution approach is introduced. In LDA one assumes the type of distribution for a single event. For frequency distribution Poisson distribution and for severity distribution normal distribution could be used as well. For the estimation methods moments and maximum likelihood methods are generally chosen. Then one obtains the aggregate loss distribution by compounding loss severity and loss frequency distribution. This approach is illustrated by an example.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 223-231